DAMPAK PANDEMI COVID-19 TERHADAP KINERJA BANK SYARIAH DI NEGARA ASEAN - Widya Rizki Eka Putri (Faculty of Economics and Business, 2023)
The purpose of this study is to provide empirical evidence on the effectiveness of government policies on the performance of Islamic banks in various ASEAN countries taken during the Covid 19 pandemic. This study uses the Capital Asset Management Earnings Liquidity (CAMEL) indicator as a measure of bank performance proxied by the ratio of CAR, ROA , NPL, BOPO and LDR. The results of this study indicate that there are differences in the CAR and BOPO ratios in Islamic banking in ASEAN countries while the ROA, NPL, and LDR ratios do not show significant differences.